TINJAUAN YURIDIS TERHADAP KEDUDUKAN PEMEGANG POLIS SEBAGAI ANGGOTA PERTANGGUNGAN PADA ASURANSI JIWA BERSAMA BUMIPUTERA 1912 PONTIANAK - FROCKY FALDIO, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2012)
AbstractAJB Bumiputera 1912 is a company that is widely used to transfer risk. Where the insured is binding to the insurer to accept a number of premium that has been agreed. Bumiputera in the insurance business is not a form of PT and CV it is a